The Influence of Role Playing Method on Civics Learning Outcomes of Students of SD Negeri 102 Kendari - Arna Juwairiyah; Arsi Arsi; Ahmad Ahmad (FKIP UNSULTRA, 2025)
This study aims to determine the influence of role-playing methods on the Civics learning outcomes of students using role-playing methods in the Civics subject at Elementary School 102 Kendari. The subjects of this study were 18 students of class IV. The study's results indicated an improvement in student learning outcomes as the pretest results showed a total of 995 with an average score of 55.11, a minimum score of 33, and a maximum score of 73. Meanwhile, the posttest results showed a total of 1521 with an average score of 84.5, a minimum score of 66, and a maximum score of 100. The conclusion from this study is that the students' learning outcomes improved.